Maxo Weberio feodalizmo samprata ir Lietuvos istorija - Norkus, Zenonas (Lietuvos istorijos studijos, 1997)
The article contains an attempt at classification of the theories of feudalism, an exposition of Max Weber’s later theory of feudalism and a discussion of the question of its applicability to the history of Lithuania in the 13th-17th centuries. The theories of feudalism are classified as building a continuum including two poles: a mimetic one and a constructivist one. The first pole is approximated by the political and legal concepts of feudalism developed by the mainstream German historians in the 19th and 20th centuries (G. von Below, H. Mitteis, O. Brunner). The second pole is approximated by the Marxist socio-economic theories of feudalism. M. Weber’s concept of feudalism is formulated in terms of political sociology and is localized in the middle of this continuum. The author suggests that the relations of political domination in the Grand Duchy of Lithuania in the 13th-17th centuries can be accounted for by applying Weber’s terms „fruendenfeudalismus," „ständische Herrschaft," and „Geschlechterstaat," but not the term „Lehnsfeudalismus."